Evaluation of Outcomes in Patients Undergoing Surgery for Brain Tumors A Prospective Clinical Study - AHMED, SAUD; REHMAN, MUHAMAAD NAEEM UR; SHARIF, HASSAAN (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Local data are still needed to optimize surgical practices, despite surgical resection being the first line of treatment for many brain tumors, as outcome variability dictates. Aim: To evaluate postoperative outcomes including neurological function, survival and quality of life in a cohort of 25 patients undergoing brain tumor surgery in a tertiary center. Methodology: It was a prospective observational study of 25 adult patients who underwent elective craniotomy for brain tumor removal during 6 months. Clinical presentation, imaging, histopathology, extent of resection, complications and 3 month functional outcomes were collected. Results: Fifteen patients were male and 10 female (mean age: 47.6 ± 11.2 years, out of 25 patients). The most common tumor types were meningioma (9 cases) and glioblastoma multiform (7 cases). Patients achieved gross total resection (GTR) in 64%. Sixty percent improved, 24 percent were stable, and 20 percent deteriorated postoperatively. In benign tumor cases, three month survival was 100%, and in malignant cases, the survival was 71.4%. Complications occurred in 4 patients (16%). Conclusion: Postoperatively, this cohort showed significant improvement in neurological function in benign tumors. Repetition of the need for surgical precision and early intervention is supported by the finding that extent of resection remains a critical determinant of outcome.